Income Analysis of Dairy Milk Production in Ciawi Livestock Research Center Bogor District - Mihrani Mihrani; Hermawan Hermawan; Fahruddin Wakano (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Ciawi livestock research center in Bogor is engaged in livestock research. The beginning of the Ciawi livestock research center was established in 1981 by Drh. Jan Nari until now. This study aims to analyze the amount of dairy milk production income in the Ciawi livestock research center, Bogor Regency. Primary data were collected based on observations at the research location, recording and interviews using questionnaires, while secondary data were obtained from the Ciawi Livestock Research Center, Bogor Regency, scientific journals and articles related to dairy milk production income. Data analysis using income and feasibility analysis. The results showed that the livestock research center in 2020 produced 28,699 liters of milk and in 2021 produced 29,783 liters of milk. In 2020 the livestock research center looks profitable at Rp. 102,393,980, and in 2021 it has decreased by Rp. 10,649,980. The R / C ratio of Dairy Cattle Farming Business at the Ciawi Livestock Research Center, Bogor Regency, West Java Province in 2020 is 1.12 and in 2021 1.01, which means that every Rp. 1 spent by the Livestock Research Center in business activities carried out is profitable or feasible to develop because the R / C Ratio > 1